Assessment of water quality status in the impact area of the "Piškornica" landfill - Mikulić, Nenad, kemijski tehnolog (Array, 2020)
Disposal of household and industrial waste at the Piškornica site began in 1982 on what was then an unmanaged landfill cell, which allowed contamination to pass into underground layers. Landfill rehabilitation was conducted between 2005 and 2013 and conformed to the environmental protection conditions and measures that were prescribed by an EIA procedure, but rehabilitation still has not been fully completed. An environmental permit was issued for rehabilitation of the landfill. The decision and environmental permit prescribed groundwater quality monitoring. Prior to these documents, five piezometers were placed into operation in 1991. The objective of this paper is to determine the potential differences in ground and surface water quality that may have resulted from landfill operations, effectiveness of the rehabilitation efforts, and the potential risk of contamination of the Ivanščak water well. The results of the research were subjected to statistical analyses (e.g., T-test and ANOVA). Based on the regional flow model, a numerical groundwater flow model and contamination transport model were created, which provided scenarios for the potential spread of pollution from the Piškornica landfill while considering different water well operation regimes. It was concluded that a) even though rehabilitation has not been completed, the groundwater quality status improved and b) none of the analysed real flow scenarios generated redirection of streamline patterns towards the Ivanščak water well. Considering future development and likely increase of the Ivanščak well capacity, the expansion of monitoring was proposed for additional measuring locations.